Driving Behavior and Safety Analysis In Context Of Weak Lane Discipline At Urban Mid-Block Section - et. al., Dr. S. Moses Santhakumar, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this research work, the behavior of driver on urban mid-block section with heterogeneous traffic conditions is evaluated. The study of vehicle to vehicle interaction plays vital role to identify the microscopic characteristics in mixed traffic streams. In this background, an access controlled mid block road section was selected for video data collection. The main objectives of this study include developing vehicular trajectory data and analyzing the lane changing and vehicle following behavior of driver on the mid block section considering the relative velocities and relative spacing between various types of vehicles under heterogeneous traffic conditions. The videos were collected from urban roadway in the Kurnool district of Andhra Pradesh. The length of the stretch is 120m and the width is 7.0 m. Data was collected by dividing the stretch into four equal parts each of length 30m. The data was extracted to know the variations in terms of longitudinal and lateral speeds, vehicle following and lane changing behavior of the drivers. The data extracted was smoothened by moving average method to minimize the human errors. Lateral amplitude of the vehicles of various types was analyzed. The study revealed that vehicles in the mixed stream, in general and in particular, Bikes and Autos particularly move substantially in the lateral direction.